Peran Pemerintah Daerah Dalam Meningkatkan Pendidikan Tentang Potensi Pariwisata Di Kabupaten Sarolangun - Rohayati, Wahyu; Karim, Navarin (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study will examine the role of local governments in improving education about tourism potential in Sarolangun Regency. This study aims to find out how the government's role in improving education about tourism for the Sarolangun community and how the government's role in managing and increasing tourism potential as well as what factors are supporting and inhibiting tourism development in Sarolangun Regency. By using qualitative descriptive research methods, the results of this study answered that the management of natural tourism objects in Sarolangun Regency by the government (Disparpora) by playing an active role as a facilitator by providing and building facilities and infrastructure, community empowerment, as a regulator, is still upheld regarding customary prohibition rules. and culture. Supporting factors in the management of Sarolangun Regency's natural attractions are the support of the local community and beautiful and pristine natural panoramas that can attract tourists to visit Sarolangun Regency's natural attractions. This study offers recommendations for the need for improvement and improvement of the quality of tourism facilities and infrastructure, such as repairing roads to tourist attractions, providing adequate transportation to tourism objects. It is necessary to add a tourism information center for the sake of convenience for tourists visiting Sarolangun Regency, It is hoped that the government will cooperate with the private sector which is the investor for the development and development of regional tourism objects so that tourism in Sarolangun Regency can succeed optimally, It is expected that the natural environment around the tourist attraction The nature of Sarolangun Regency can be maintained so that this natural tourist attraction can still provide comfort for visitors.